MENGEMBANGKAN KREATIFITAS PESERTA DIDIK/ INKLUSIF: Studi Kritis Manajemen SDM Guru - Zainur Arifin; Muhammad Asrori Ma'sum (Muróbbî: Jurnal Ilmu Pendidikan, 2020)
Human resource management is the policy of managing human resources in an organization to achieve a goal, which is included in human resource management activities in the educational organization process, namely planning, recruitment, selection, placement, training and development. Creativity is how to produce or increase the highest possible results of goods and services by utilizing resources efficiently. Creativity is to produce output and efficient use of input resources. Students are people who are not yet mature and have a number of basic potentials (fitrah) that need to be developed. Students are one of the most important components in education, without which the educational process will not be carried out. Therefore, the understanding of students needs to be known and understood in depth by all parties. So that in the educational process, there will be no deviations too far from the planned educational goals. Education and training through development can help the process of improving job skills, theory-oriented education, carried out in the classroom. SLB teachers are always included whenever there are activities such as seminars, scientific forums, training, workshops, training held by certain institutions, then besides that there is also teacher training from within the institution, namely calling psychologists for training for teachers, the advantages are There is training for teachers who are located in their own schools, then from outside also participate in the implementation of the training, which aims to improve teacher competence and teacher professionalism in general.